The Painting of Modern Life : 1960s to now. - Christov-Bakargiev, Carolyn; Herbert, Martin; Rugoff, Ralph; Schwabsky, Barry; Silverman, Kaja (London : Hayward Publishing, 2007)
Artschwager, Richard ; Bechtle, Robert ; Celmins, Vija ; Doig, Peter ; Dumas, Marlene ; Eggerer, Thomas ; Eisler, Judith ; Gertsch, Franz ; Hamilton, Richard ; Havekost, Eberhard ; Hockney, David ; Kahrs, Johannes ; Kandl, Johanna ; Kippenberger, Martin ; Liu Xiaodong ; Morley, Malcolm ; Peyton, Elizabeth ; Pistoletto, Michelangelo ; Richter, Gerhard ; Sasnal, Wilhelm ; Tuymans, Luc ; Warhol, Andy
2 volumes: 1 engelstalig, 1 italiaans
The Painting of Modern Life, The Hayward, London, 4 October - 30 December 2007
The Painting of Modern Life, Castello di Rivoli, Museum of Contemporary Art, Turin, 6 February - 4 May 2008
biog. per kunstenaar, ind. tent., gr. tent., bibliog. p. 182-191
2 volumes: 1 engelstalig, 1 italiaans
boek